Perilaku Makan dengan Kejadian Sindrom Premenstruasi pada Remaja - Nurmiaty Siswanto Agus Wilopo, Toto Sudargo (Berita Kedokteran Masyarakat (BKM), 2011)
Eating Behavior and the Prevalence of Premenstrual Syndrome in TeenagersBackground: Problems commonly encountered by teenagers in relation to menstruation are dysmenorrheal and premenstrual syndrome. Some recent studies reveal that micronutrients (calcium, magnesium and vitamin D) have an important role in causing disorder of mood and behavior during premenstruation. Teenagers generally consume foods with low nutrients and have a diet that causes lack of nutrient intake leading to menstrualdisorder.Objective: To identify the association between eating behavior and the prevalence of premenstrual syndrome in teenagers at District of Purworejo.Method: This was a case control study with quantitative approach. Subject of the study were students of SMKN 3 and SMAN I Purworejo. Analysis stage I was made to identify the prevalence of premenstrual syndrome (n=749). Analysis stage II was made to identify the association between eating behavior and the prevalence of premenstrual syndrome; the comparison between samples of cases and control was 1:1 (n=160).Result: The prevalence of premenstrual syndrome in teenagers was 24.6%. The test in eating behavior and premenstrual syndrome showed the result was statistically significant. When variable of stress was controlled, the risk for premenstrual syndrome was 2.3 times greater. The result of logistic regression analysis on nutrient intake showed that fat and potassium had the most dominant effect to the incidence of premenstrual syndrome with standardized coefficient value as much as 0.7982 and 0.7834 subsequently.Conclusion: Unhealthy eating behavior increased risk for premenstrual syndrome 2.3 times greater. Intake of fat and potassium most dominantly affected premenstrual syndrome.Keywords: eating behavior, premenstrual syndrome, teenagers